John Dewey and the dialogue between architecture and neuroscience. Issue 4 (12th May 2016) - Robinson, Sarah
Abstract : Sustainability is the most significant force to change architecture since the breakthrough of modernism a century ago. So far the contributions of architects to this mandate have largely amounted to technological interventions. Yet the urgent call for sustainability demands going beyond merely technological solutions to modify behavioral patterns, cultural habits and even our deeply ingrained ideas about ourselves. The very notion that architecture could modify behavioral patterns, or the sedimentation of habits seems far-fetched in an epistemological framework that has drawn strict lines between outside and inside, subject and object, body and mind — all the dualities that the cognitive and neurosciences have been gradually working to undermine. Our practice as architects has been unconsciously shaped by centuries of formalist thinking that have turned buildings into inanimate objects; a habit of thinking that has weakened our role and contributed to the sense that architecture is a luxury item, one among many consumable commodities — though we can no longer deny that it is the very fabric of our survival and flourishing. Further, the once healthy plurality of our architectural theory has left us without a coherent philosophical framework with which to confront the climate crisis. For John Dewey, theory and practice were not ontologically separate domains, but two distinct yet inseparable and necessary aspects of engaging in the world. This essay explores how Dewey's pragmatic philosophy could help to build a theoretical framework that would allow us to apply and integrate the findings of the cognitive and neurosciences into our architectural practice and education, so that we might respond not only to the constraints and opportunities of the given context — site, program and energy resources—but also to the limits and affordances of our perceptual systems and the whole of our body and mind.